Catalytic water oxidation of wastewater containing acetic acid - Hanifan, Abd Jalil (2013)
Treatment of wastewater containing significant amount of acetic acid has been recognized as a significant expense to the industry and the environment. The conventional ways usually requires a lot of energy and long residence time. Therefore, by using the catalytic water oxidation process which is done in normal operating condition, the process of wastewater treatment can be done in a more energy and cost efficient manner. The main objective of this experiment is to synthesize and characterize the palladium over the aluminium oxide and then to oxidize the acetic acid and study the effect of important parameters to the wastewater treatment process. The catalyst is synthesized using the wet impregnation method of palladium chloride with the support. For the reaction purpose, a 3-necked flask was used as the batch reactor. The catalyst synthesized is in crystalline form and consists of large surface area. It was found that in overall, the catalyst was able to oxidize the acetic acid at the given condition, such as that increasing the temperature and acetic acid concentration will increase the oxidation process.